Cayenne pepper and shallot price volatility, inflation, and regional economic growth in Palopo City: An Islamic economics perspective - Asriaty, Asriaty; Ahmad Syarief Iskandar; Ishak, Ishak (Universitas Islam Indonesia, 2026)
IntroductionPrice fluctuations in strategic food commodities can influence inflation, household purchasing power, producer income, and regional economic growth. In Palopo City, cayenne pepper and shallots are widely consumed and traded, making their price movements important for local economic stability. However, city-level studies that integrate commodity price volatility, inflation transmission, regional growth, and Islamic economic insights remain limited.ObjectivesThis study analyzes fluctuations in cayenne pepper and shallot prices, examines their relationship with inflation and economic growth in Palopo City, and identifies relevant stabilization measures. It also interprets the findings through Islamic economic principles, including public welfare, wealth protection, fair market governance, and the prevention of hoarding.MethodThe study employed a quantitative explanatory design using annual secondary data for 2021–2025. The variables included average cayenne pepper prices, shallot prices, inflation, and regional economic growth measured through Gross Regional Domestic Product growth. Descriptive trend analysis was combined with multiple linear regression to assess the simultaneous relationship between commodity prices, inflation, and economic growth.ResultsCayenne pepper prices showed an overall upward trend and reached their highest level in 2025, while shallot prices declined sharply in 2023 before recovering. Inflation peaked in 2022 and increased moderately again in 2025. Cayenne pepper prices appeared more closely associated with short-term inflationary movements than shallot prices. The regression analysis indicated that cayenne pepper prices, shallot prices, and inflation were jointly associated with regional economic growth. The findings also showed that production conditions, weather, input availability, distribution constraints, seasonal demand, and policy responses shaped commodity price movements.ImplicationsRegional price stabilization should combine improved production planning, shorter distribution chains, stronger logistics and storage, market operations, digital price information, and coordinated action among farmers, traders, distributors, and government agencies. Islamic economic principles support such intervention when it protects consumers and producers without eliminating legitimate market incentives.Originality/NoveltyThis study contributes city-level evidence by integrating commodity-specific price fluctuations, inflation, regional economic growth, and Islamic economic perspectives within the post-pandemic context of Palopo City.